Assessing Maternal Satisfaction and Neonatal outcomes in Patients Scheduled for Elective Caesarean Section under Spinal Anaesthesia at Shah Medical Center Swat - Khan, Sami Ullah; Naseem, Chanda; Tayyeb, Muhammad; Hussain, Israr; Abdul Aziz; Shahid, Omama (Indus Journal of Bioscience Research, 2025)
Introduction: Maternal satisfaction and baby outcomes are key indications of spinal anesthesia cesarean section quality. This study examined mother satisfaction and neonatal outcomes in elective cesarean sections at Shah Medical Center, Swat. Methodology: Patients scheduled for elective spinal anesthesia cesarean sections were studied cross-sectionally. A standardized questionnaire examined maternal satisfaction with pain management, preoperative information, anesthetic team support, and overall experience. Neonatal outcomes were assessed by APGAR ratings at 1, 5, and 7 minutes. Statisticians examined relationships between satisfaction, demographics, and newborn outcomes. Results: The study included 267 individuals with a mean mother age of 29.6 ± 5.3 years and a mean gestational age of 38.4 ± 1.2 weeks. The majority of participants were multigravida (66.7%), housewives (83.5%), and belonged to the intermediate socioeconomic category (52.4%). Neonates primarily exhibited normal APGAR scores, with 78.7% at 1 minute, 91.8% at 5 minutes, and 96.3% at 7 minutes. Elevated mother satisfaction (53.9%) correlated with markedly improved infant APGAR scores at all intervals (p < 0.001). Effective pain treatment (OR: 4.5, p < 0.001), preoperative information (OR: 2.3, p = 0.002), and a supportive anesthesia team (OR: 3.1, p < 0.001) were significant predictors of satisfaction. Gestational age (p < 0.001), parity (p = 0.031), and socioeconomic level (p = 0.015) were significant determinants of satisfaction. Conclusion: Effective pain management, preoperative education, and supportive anesthesia care greatly increased maternal satisfaction with spinal anesthesia during cesarean sections. High satisfaction was linked to better newborn APGAR scores and outcomes.